Pengaruh Kurikulum Merdeka Belajar Terhadap Keberhasilan Belajar Siswa SMA/MA Di Kota Cirebon - Gayatri , Ratna; Suklani (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
This type of research is qualitative research which contains descriptions and explanations related to the implementation of the new curriculum, namely the independent learning curriculum. The main purpose of this research is to reveal what problems occur in implementing the new curriculum. There are so many problems that are obtained. The result of this research is that some students feel new things with this curriculum. The new thing is the P5 project at the end of each lesson. However, some students are actually burdened and feel objections to the implementation of the independent learning curriculum. In addition to students, teachers also feel the same way because of the lack of teaching materials that can be used as examples for the learning process. So that teachers have to be extra in finding sources and new ideas in implementing and making P5 projects. The conclusion of this research is that the government, which focuses on education, must fix the implementation of the curriculum, because not all schools are able to implement it due to the lack of facilities which is the main factor.